The Inventory of Soil Ants in Residential Area of Palembang - Ari Saputra; Zainal Arifin; Riyanto Riyanto (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2021)
The purpose of this research is to find out the species of soil ants in the residential area. The sampling method is hand collecting and baited trap (tuna and honey). There are 8 species found: Acanthomyrmex sp., Solenopsis germinata, Monomorium pharaonis, Pheidole megacephala, Paratrechina longicornis. Tapinoma melanocephalum, Camponotus ligniperda, Diacamma intricatum. The most numerous species, namely Pheidole megacephala and the least species, namely Diacamma intricatum. Ant species diversity tends to increase, as human activity decreases